GAMBARAN PENGETAHUAN TENTANG PENGENDALIAN INFEKSI SILANG PADA KOMUNITAS TEKNISI GIGI DI KOTA BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2020)
Infectious diseases in dental health services can be transmitted from one person to another through direct or indirect contact. Some diseases that can be transmitted are tuberculosis, HIV, hepatitis, herpes, and other diseases whose pathogenic microorganisms are in the oral cavity. Dental technicians are one of the health workers who are at risk of cross-infection due to their work. This research is a descriptive study that aims to find out the description of knowledge about cross infection control in the dental technician community in the city of Bandung. Samples were 4 dental technicians who worked in 3 laboratories in Bandung. Data was collected by filling out a questionnaire about controlling cross infection which is presented online in the form of Google Form. Two technicians have a sufficient level of knowledge in the category, and 2 other technicians in the good category. The problem of cross-infection control that is poorly understood by dental technicians is about the source of infection that has the most potential to transmit disease and the disinfection of printed materials. Dental technicians need to be given sufficient knowledge about cross infection control.